Economic behavior: Evolutionary vs. behavioral perspectives - Ulrich Witt (Max Planck Institute of Economics, 2010)
An evolutionary perspective on economic behavior has to account for the influences that the human genetic endowment has on the choices the agents make. Likely to have been fixed in times of fierce selection pressure, this endowment is presumably adapted to the living conditions of early humans. If at all, behavioral economics accounts for its influences on economic decision making in a way similar to the approach taken by evolutionary psychology, i.e. by focusing on decision heuristics and their tensions with modern rationality standards. In an evolutionary perspective, that focus needs to be extended so as to also embrace the motivational underpinnings of economic behavior. In the language of economics this means to inquire into the agents' preferences and to explain how they relate to the human genetic endowment and how they change over time. The paper discusses several implications of such an extension.
urn:nbn:de:gbv:27-20110628-150917-6
Keywords: A12; B25; B52; D01; D03; D63; O10; 330; behavioral economics; evolutionary economics; Darwinism; decision heuristics; preferences; development; growth; welfare; Verhaltensökonomik; Evolutionsökonomik; Bioökonomik; Theorie